(untitled) (Studia Prawnicze / The Legal Studies, 1984)
In the first part of the article the evolution of control procedure has been presented, the basis of which are communications on the violation of human rights. Then the author critically analyzes control procedure which has been regulated by resolutions of the Economic and Social Council. Special attention has been paid to the resolution 1503 (XLVIII). The competence of the Commission on Human Rights and the Sub-Commission on the Prevention of Discrimination and Protection of Minorities was discussed in detail. Finally, the author discusses international initiatives the aim of which was to create new organs and new procedures of control over the effective enjoyment of human rights. The discussed control system has emerged in many years’ discussions and is a result of a compromise between advocates and opponents of international control. According to the author, as a result of the compromise, norms regulating control Procedure are too general and competence of international organs is vague. The author agrees with the opinion expressed by Many states and formulated in the doctrine that the increase of the number of control organs and procedures does not automatically guarantee general effective enjoyment of human rights. Thus, she thinks that tendencies to intensify the actions in the field of promotion of human rights are right and justified. As far as their protection is concerned, the main task is to increase the effestiveness of existing control procedures.